Effectiveness of effective microorganism (Lactobacillus casei) in growth development of rice variety (MR219) / Mohammad Faiz Sabri - Sabri, Mohammad Faiz (Faculty of Plantation and Agrotechnology, 2019)
Effective microorganism (EM) is microbial inoculants that can promote the growth performances of plant and in other ways can enhance the soil fertility. This study was conducted to know the effectiveness of EM that contains Lactobacillus casei for growth performance of rice that has been planted in Greenhouse at UiTM Jasin in complete randomized design (CRD) based on 4 treatments and 4 replications. The rice variety that has been used for this study is MR 219 from MARDI which is the popular variety among farmers in Malaysia especially at the granary area. Lactobacillus casei is the pro biotic bacteria obtained from Yakult. EM that has been produced can be used towards rice between one to two weeks. This is because EM condition that have bad odor may have poor effectiveness towards samples that have been study. The four types of treatments used in this experiment which are; (1) control, (2) 1.2 x 109 CFU in 100 ml of EM, (3) 3.6 x 109 CFU in 300 ml of EM and (4) 6 x 1010 CFU in 500 ml of EM respectively. It involved 16 samples of rice plants (MR219) that have been planted in the pots. This study shows that treatment with 6 x 109 CFU in 300 ml of EM (Lactobacillus casei) give more positive result compared to other treatments. Average of plant height, average of number of tillers, and average of number of grains per panicles were recorded. The results indicated that the optimum amount of EM concentration that has been applied at rice can enhance the growth performance of rice (MR219).